(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify body patterns and their relationship to sports` injuries among the players in the Jordanian Women’s Professional Football League. The researchers used the descriptive survey method which fits the nature and the goals of the study. The study sample consisted of (48) female players who were purposively selected, and and who represented (7) professional clubs for the 2019/2020 season.The researchers used in this study the percentages, frequencies, and multiple analysis of variance (Multiple Anova) The results show that the most common body pattern is the slim since; there are 23 footballers who belong to this pattern with a percentage of (47.9%) from the total number of the injured footballers. The most common injury found among the injured footballers was the knee ligament injury (anterior cruciate ligament tear), which represented the highest percentage of the total number of the injuries with a percentage of (24.74%). The most common cause of the injuries was roughness and violent play, which came first with a percentage of ( 47.42%). The results show the existence of statistically significant differences at the level of significance (α≤ 0.05) in the number of sports injuries that the footballers were exposed to depending on the variables of physical pattern, the period of injury, years of experience, and playing center); the differences due to the variable of psyical patternwere in favor of the fatty pattern and in favor of the competition period. As for the variable of experience, the differences were in favor of the less experience (less than 5 years) and in favor of the midfielder. The researchers recommended not neglecting injuries, no matter how simple, in order to avoid future complications in which the injury develops into a chronic injury that will be difficult to treat in the future.